Taste Masking of Pharmaceutical Formulations: Review on Technologies, Recent Trends and Patents: Pharmaceutical Science-Pharmaceutics for effective drug dosage - Prashant Thakker; Jigna Shah; Tejal Mehta; Gaurav Agarwal (International Journal of Life Science and Pharma Research, 2022)
The majority of active pharmaceutical ingredients (APIs) found in oral dosage forms have unpleasant or obnoxious taste. Taste is one of the important parameters which governs patient compliance and also decides the success of a product in the market. Undesirable taste or the bitter taste is a major challenge that formulation scientist faces with many drugs. Hence, oral administration of bitter drugs is a big challenge, especially for pediatric patients. This article focuses on various tastes masking techniques by which the characteristics of the dosage form are improved and better patient compliance can be achieved. The article also discusses various recent taste masking evaluation techniques used in oral pharmaceutical formulations. The pharmaceutical companies are now engaged in developing novel techniques to overcome the problem of taste masking by numerous patents filed for taste masking. Lists of patents for taste masking are discussed and how these patents overcome the limitations of conventional approaches of taste masking is also reviewed. The present article also emphasizes various patented platform technologies based on different techniques used for taste masking. The important features and principles involved in taste-masking approaches of various patented technologies are also discussed. A better understanding of these new patents and patented technologies will help formulation scientists to select the most suited technology for development of new products with improved taste.